Some outcomes of flexible learning at the University of Otago 1996-98 - Andrew Higgins (Flexible Learning Association of New Zealand, 2012)
The purpose of this report is to examine the adoption and implementation of flexible learning initiatives at the University of Otago. Altogether there have been 169 projects of varying size incorporating technologies in teaching. Twenty-eight of these have been designated specifically as flexible learning projects. The report discusses definitions surrounding the term 'flexible learning', the role it plays in helping change teaching strategies and presents five brief case studies which describe the implementation and outcomes of some flexible learning projects.